Hexagonal mesoporous silica modified with 2-mercaptothiazoline for removing mercury from water solution - Evangelista, Sheila M.; DeOliveira, Ediniar; Castro, Gustavo R.; Zara, Luiz F.; Prado, Alexandre G. S. (Elsevier B.V., 2007)
A method for the attachment of 2-mercaptothiazoline (MTZ) to modified silica gel has been developed. In the first step, a new silylant agent was synthesized, named SiMTZ, by the reaction between MTZ molecule and chloropropyltrimethoxysilane (SiCl). SiMTZ and tetraethylortosilicate were co-condensed in the presence of n-dodecylamine, a neutral surfactant template, to produce a modified ordered hexagonal mesoporous silica named HMTZ. The modified material contained 0.89 +/- 0.03 mmol of 2-mercaptothiazoline per gram of silica. FT-IR, FT-Raman, Si-29- and C-13-NMR spectra were in agreement with the proposed structure of the modified mesoporous silica in the solid state. HMTZ material has been used for divalent mercury adsorption from aqueous solution at 298 I K. The series of adsorption isotherms were adjusted to a modified Langmuir equation. The maximum number of moles of mercury adsorbed gave 2.34 +/- 0.09 mmol/g of material. The same interaction was followed by calorimetric titration on an isoperibol calorimeter. The HMTZ presented a high capacity for the removal of the contaminant mercury from water. The Delta H and Delta G values for the interaction were determined to be -56.34 +/- 1.07 and -2.14 +/- 0.11 kJ mol(-1). This interaction process was accompanied by a decrease of entropy value (- 182 J mol(-1) K-1). Thus, the interaction between mercury and HMTZ resulted in a spontaneous thermodynamic system with a high favorable exothermic enthalpic effect. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: silica; calorimetry; mercury